Insulin-like growth factor role in determining the anti-cancer effect of metformin: RCT in prostate cancer patients - Vita Birzniece (Endocrine Connections, 2022)
Objective: Androgen deprivation therapy (ADT), a principal therapy in patients with prostate cancer, is associated with the development of obesity, insulin resistance, and hyperinsulinemia. Recent evidence indicates that metformin may slow cancer progression and improves survival in prostate cancer patients, but the mechanism is not well understood. Circulating insulin-like growth factors (IGFs) are bound to high-affinity binding proteins, which not only modulate the bioavailability and signalling of IGFs but also have independent actions on cell growth and survival. The aim of this study was to investigate whether metformin modulates IGFs, IGF-binding proteins (IGFBPs), and the pregnancy-associated plasma protein A (PAPP-A) – stanniocalcin 2 (STC2) axis. Design and methods: In a blinded, randomised, cross-over design, 15 patients with prostate cancer on stable ADT received metformin and placebo treatment for 6 weeks each. Glucose metabolism along with circulating IGFs and IGFBPs was assessed. Results: Metformin significantly reduced the homeostasis model assessmen t as an index of insulin resistance (HOMA IR) and hepatic insulin resistance. Metformin also reduced circulating IGF-2 (P < 0.05) and IGFBP-3 (P < 0.01) but increased IGF bioactivity (P < 0.05). At baseline, IGF-2 correlated significantly with the hepatic ins ulin resistance (r2 = 0.28, P < 0.05). PAPP-A remained unchanged but STC2 declined significa ntly (P < 0.05) following metformin administration. During metformin treatment, change in HOMA IR correlated with the change in STC2 (r2 = 0.35, P < 0.05). Conclusion: Metformin administration alters many components of the circulating IGF system, either directly or indirectly via improved insulin sensitivity. Reduction in IGF-2 and STC2 may provide a novel mechanism for a potential metformin-induced antineoplastic effect.